2007
DOI: 10.1158/0008-5472.can-07-0519
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of B-Cell Lymphomas by Methylseleninic Acid Involves Nuclear Factor-κB Inhibition and the Rapid Generation of Other Selenium Species

Abstract: Although recent reports suggest that selenium can modulate the activity of cytotoxic drugs, the mechanism underlying this activity remains unclear. This has been investigated using a panel of human B-cell lymphoma cell lines. The cytotoxic effects of chemotherapeutic agents (e.g., doxorubicin, etoposide, 4-hydroperoxycyclophosphamide, melphalan, and 1-B-D-arabinofuranosylcytosine) were increased by up to 2.5-fold when combined with minimally toxic concentrations (EC 5-10 ) of the organic selenium compound, met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…HIF-1 expression is also regulated by NF-k itself subject to acetylation/deacetylation modifications of the p65, and possibly p52, subunits which affects DNA binding [2]. We have previously reported the NF-k inhibitory activity of MSA [14].…”
Section: Effect Of Msa On Hif-1α Expression and Vegf Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIF-1 expression is also regulated by NF-k itself subject to acetylation/deacetylation modifications of the p65, and possibly p52, subunits which affects DNA binding [2]. We have previously reported the NF-k inhibitory activity of MSA [14].…”
Section: Effect Of Msa On Hif-1α Expression and Vegf Secretionmentioning
confidence: 99%
“…Regarding diffuse large B-cell lymphoma (DLBCL), our department has reported that serum Se at diagnosis is predictive of outcome in patients with B-cell non Hodgkin lymphoma, the majority of whom had DLBCL [18]. In addition, in vitro studies have demonstrated that high concentrations of Se are cytotoxic [17], whilst non-toxic concentrations can sensitise cells to the cytotoxic effects of chemotherapeutic agents [14]. The precise mechanism of Se action is not clear and differs based on the chemical form, dose/concentration and tumour type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been investigated using a panel of human B-cell lymphoma cell lines. Taken together, these results show that the NF-B pathway is one target for methylselenic acid (MSA) underlying the interaction between MSA and chemotherapy [201].…”
Section: Seleniummentioning
confidence: 79%
“…12) However, selenium has also been shown to inhibit cell growth, 13,14) induce cell death 15) or apoptosis, 16,17) and suppress NF-κB. 18,19) Although the essential roles of selenium in immune cell functions have already been reported, the functions and underlying mechanisms have yet to be elucidated due to these inconsistencies. Selenium has been shown to have anticancer effects at concentrations higher than nutritional requirements, 20,21) and these may be mediated through cell cycle arrest, apoptosis, and/ or the toxic effect.…”
mentioning
confidence: 99%